The role of DNA methylation in the disorders of bone metabolism - B. I. Yalaev; A. V. Tyurin; R. Y. Mirgalieva; R. I. Khusainova (Вавиловский журнал генетики и селекции)
Osteoporosis is one of multifactorial diseases, it develops from interactions between the genetic component and the environment. However, the universal epigenetic markers of osteoporosis are not yet defined. Finding the risk factors will predict the risk of osteoporosis at the preclinical stage, help define the course and severity of the disease, and develop preventive measures based on them to reduce the risk of fractures. Expanding knowledge in the field of bone biology, especially in the genetics of osteoporosis and osteoimmunology, showed that osteoporosis is a disease that occurs not only due to hormonal or mechanical disorders, but also as a clinically and genetically heterogeneous disease, and there are still unknown pathogenetic links in its structure. Decreases in bone mass and matrix mineralization as well as changes in bone microarchitecture can have different pathogenetic patterns of development and, moreover, there are unknown links of the pathogenesis of osteoporosis. It is possible that DNA methylation is one of these links and a mechanism for epigenetic regulation of gene expression. Evidence exists that this mechanism alongside regulatory miRNAs and post-translational modifications makes a significant contribution to the central processes of bone remodeling; however, the results of various studies vary greatly, and, therefore, there is a need to understand the significance of the accumulated data and to make them consistent. The purpose of this review is to compile and systematize data on the role of DNA methylation in bone metabolism in normal and pathological conditions, in the formation of osteoporosis, and to assess achievements and trends in this field of research and technologies for studying DNA methylation.